Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1002/1097-0142(19860915)58:6<1246::aid-cncr2820580612>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistologic analysis of the phenomenon of spontaneous regression of numerous flat warts

Abstract: Among various tumors induced by human papilloma virus (HPV), flat warts are unique in that they show a systemic regression phenomenon after sudden occurrence of inflammation in all the tumors, leaving permanent immunity to flat warts in the host. When studied immunohistochemically, the presence of HPV antigen using papilloma virus genus-specific antiserum in 31 cases of regressing flat warts was not found; whereas it was demonstrated in the nuclei of upper epidermal cells of ordinary flat warts in 12 of 19 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…The majority of these cancers expresses the HPV16-derived E6 and E7 oncoproteins (2), which are therefore attractive targets for T cell-mediated immunotherapy (3). Several observations, such as the spontaneous regression of most premalignant cervical lesions (4 -6) and the infiltration of CD4 ϩ T cells and macrophages in regressing genital warts (7,8), suggest that therapeutic vaccination may prevent progression from oncogenic HPV infection through cervical intraepithelial neoplasia to cervical cancer. This notion is supported by the fact that an increase in HPV infection was found in immunosuppressed (9) and immunodeficient (10) patients.…”
mentioning
confidence: 99%
“…The majority of these cancers expresses the HPV16-derived E6 and E7 oncoproteins (2), which are therefore attractive targets for T cell-mediated immunotherapy (3). Several observations, such as the spontaneous regression of most premalignant cervical lesions (4 -6) and the infiltration of CD4 ϩ T cells and macrophages in regressing genital warts (7,8), suggest that therapeutic vaccination may prevent progression from oncogenic HPV infection through cervical intraepithelial neoplasia to cervical cancer. This notion is supported by the fact that an increase in HPV infection was found in immunosuppressed (9) and immunodeficient (10) patients.…”
mentioning
confidence: 99%
“…Cellmediated immune responses play an important role in antitumor responses. 6,7) It has been demonstrated that immunization with E7 or L1DE7 1-60 protein activates CTL responses and induces tumor protection in vivo. 13,22) In our study, immunization with mE6 1-120 /mE7 1-60 also elicited specific CTLs, which was demonstrated by the fact that these CTLs specifically lysed target cells expressing E6 and E7, but not Lewis lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from immunosuppressed patients (Alloub et al, 1989;Kent et al, 1987;Sillman et al, 1984;Lutzner et al, 1983;Mullen et al, 1976) and regressing warts (Fierlbeck et al, 1989;Aiba et al, 1986) suggests an important role for the immune system in papillomavirus infections.…”
mentioning
confidence: 99%